2018
DOI: 10.5539/ep.v7n1p36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonal Variation on Informal Waste Collection in Ibadan, South-west Nigeria

Abstract: Despite the active participation of informal waste collectors (IWCs) in waste management in Ibadan, south-west Nigeria, a major observed challenge to effective operation of this group of workers is the variation in the seasons of the year and their accompanying weather futures. This study investigated the effects of seasonal changes on the types and volume of waste handled by the informal waste collectors, level of patronage and income earned in the five municipal local government areas of Ibadan. A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
2
Order By: Relevance
“…The assessment of industrial waste generated in Lagos shows that across all sample locations, more industrial waste is generated during the dry (harmattan) season when compared to the amount of industrial waste generated during the wet (rainy) season. This finding is in contrast with the findings of Wahab and Ola (2018), who found that there was more waste generated in the wet season in Ibadan, South West Nigeria. This contrast in the findings of this study and that of Wahab and Ola (2018) may be explained by Lagos being a flood prone area, as such more production and hence more waste is generated in the dry season when the rains and floods have subsided.…”
Section: Discussion Of Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The assessment of industrial waste generated in Lagos shows that across all sample locations, more industrial waste is generated during the dry (harmattan) season when compared to the amount of industrial waste generated during the wet (rainy) season. This finding is in contrast with the findings of Wahab and Ola (2018), who found that there was more waste generated in the wet season in Ibadan, South West Nigeria. This contrast in the findings of this study and that of Wahab and Ola (2018) may be explained by Lagos being a flood prone area, as such more production and hence more waste is generated in the dry season when the rains and floods have subsided.…”
Section: Discussion Of Resultscontrasting
confidence: 99%
“…This finding is in contrast with the findings of Wahab and Ola (2018), who found that there was more waste generated in the wet season in Ibadan, South West Nigeria. This contrast in the findings of this study and that of Wahab and Ola (2018) may be explained by Lagos being a flood prone area, as such more production and hence more waste is generated in the dry season when the rains and floods have subsided. In terms of the total amount of industrial wastes generated, Ikorodu accounts for most of the industrial waste generated followed by Ikeja, Oshodi, Alaba/Ojo and Surulere.…”
Section: Discussion Of Resultscontrasting
confidence: 99%
“…Additionally, seasonal variations have also influenced the informal waste collectors, especially in their collected waste amount and income earned (Wahab and Ola, 2018). Therefore, it is also assumed that seasonal variation could affect the informal recycling shops, too.…”
Section: Main Challenges Of Informal Recycling Shopsmentioning
confidence: 99%